Implementation of Religious Character Education in Elementary School Students: Implementasi Pendidikan Karakter Religius pada Siswa di Sekolah Dasar - Sari, Defi Noviatul; Amrullah, Muhlasin (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the implementation of religious character education as well as the supporting and inhibiting factors at SDI Darul Hikmah Krian. The research uses qualitative methods. The research subjects were the principal, class III homeroom teacher, and students at SDI Darul Hikmah Krian. Collecting data using observation, interviews and documentation. Checking the validity of the data using source triangulation and technical triangulation. The results obtained are that the implementation of religious character education in class III students is applied through the method of habituation of students' religious activities on a regular basis. The supporting factors are full support from parents of students, commitment between teachers and guardians of students in monitoring the religious activities of students in the home environment using activity liaison books, and adequate facilities that support the implementation of activities. While the inhibiting factors are human resources or the teachers themselves, the surrounding environment and infrastructure facilities that have not been realized.